Evaluating Mass Rapid Transit (MRT) Service Quality According to Customers Age Group of Varying Travel Pattern - Norhisham S.; binti Samsudin N.S.S.; Ismail N.; Mardi N.H.; Abu Bakar M.F.; Azlan N.N.I.M.; Ron Buking R.A.C. (Springer Science and Business Media Deutschland GmbH, 2023)
Developing countries; Mass transportation; Quality control; Quality of service; Rapid transit; Sales; Surveys; Age; Age groups; Importance-performance analyse; Importance-performance analysis; Mass rapid transit; Perceived service qualities; Public transportation; Rail transportation; Service Quality; Transit services; Cluster analysis